The first Chinese National Union of Real‐world Gynaecological Oncology Research and Patient Management Platform: A retrospective study. (9th December 2022) - Zeng, Shaoqing; Chi, Jianhua; Liu, Jiahao; Jiao, Xiaofei; Liu, Xingyu; Yu, Yang; Li, Ruyuan; Huo, Yabing; Ma, Guanchen; Zhao, Yingjun; Wang, Li; Zhou, Qi; et al.
Abstract: Objective: To produce high‐quality, real‐world evidence for oncologists by collating scattered gynaecologic oncology (GO) medical records in China. Design: Retrospective study. Setting: The National Union of Real‐world Gynaecological Oncology Research and Patient Management Platform (NUWA platform). Sample: Patient‐centred data pool. Methods: The NUWA platform integrated inpatient/outpatient clinical, gene and follow‐up data. Data of 11 456 patients with ovarian cancer (OC) were collected and processed using 91 345 electronic medical records. Structured and unstructured data were de‐identified and re‐collated into a patient‐centred data pool using a predefined GO data model by technology‐aided abstraction. Main Outcome Measures: Recent treatment pattern shifts towards precision medicine for OC in China. Results: Thirteen first‐tier hospitals across China participated in the NUWA platform up to 7 December 2021. In total, 3504 (30.59%) patients were followed up by a stand‐alone patient management centre. The percentage of patients undergoing breast cancer gene ( BRCA ) mutation tests increased by approximately six‐fold between 2017 and 2018. A similar trend was observed in the administration rate of poly(ADP‐ribose) polymerase inhibitors as first‐line treatment and second‐line treatment after September 2018, when olaparib was approved for clinical use in China. Conclusion: The NUWA platform has great potential to facilitate clinical studies and support drug development, regulatory reviews and healthcare decision‐making.